2013
DOI: 10.1016/j.chemosphere.2012.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of toxic effluents released from PVC carpet under different fire conditions

Abstract: A large number of investigations have been reported on minimising the PAH and PCDD/F yields during controlled combustion, such as incineration. This study is an attempt to quantify acute and chronic toxicants including PAH and PCDD/F in conditions relating to unwanted fires. This paper investigates distribution patterns of fire effluents between gas and aerosol phase, and the different particle size-ranges produced under different fire conditions. PVC carpet was selected as the fuel as a precursor for both PAH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 16 publications
0
13
0
2
Order By: Relevance
“…The most extensively studied class of combustion products was inorganic gases. A small number of studies also investigated other pollutants including VOCs [27,31,32,35,39,44], PAHs [27][28][29]31,33,37,38,[45][46][47][48], dioxins and/or other persistent organic pollutants [33,40,47,[49][50][51][52] and particle size distribution [45,53]. Organic compounds were considered to be a potential hazard, but in most studies individual compounds have not been identified or quantified.…”
Section: Introductionmentioning
confidence: 99%
“…The most extensively studied class of combustion products was inorganic gases. A small number of studies also investigated other pollutants including VOCs [27,31,32,35,39,44], PAHs [27][28][29]31,33,37,38,[45][46][47][48], dioxins and/or other persistent organic pollutants [33,40,47,[49][50][51][52] and particle size distribution [45,53]. Organic compounds were considered to be a potential hazard, but in most studies individual compounds have not been identified or quantified.…”
Section: Introductionmentioning
confidence: 99%
“…Using the steady state tube furnace (ISO TS 19700), the generation of isocyanates from materials such as PUR mattresses and insulation materials as well as PVC carpets and wood board were analysed [11,47]. A correlation between the magnitude of the obtained yields for isocyanates from the PUR materials from the well-ventilated stage and yields from PUR from the cone calorimeter was reported.…”
Section: Assessment Of Fire Toxicitymentioning
confidence: 99%
“…In laboratory animals and human lung cell lines they have been shown to cause the increased oxidative stress resulting in regeneration of reactive oxygen species (ROS) in biological systems, and associated with cancer, pulmonary and other diseases [62,63]. The formation of potentially toxic particulates, polycyclic aromatic hydrocarbons, and isocyanates, and their distribution between gas phase and solid phase for different building material fires has been investigated [47].…”
Section: Assessment Of Fire Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the early period of co-combustion, benzene rings fixed in molecular chain of PS would be broken, so did lateral chloride of PVC in the same time. According to related researches [25,26], the process of dechlorination would occur before the combustion of PVC, and benzene and imidazole could be found during this process. Dechlorination could be regarded as the stage of devolatilization during PVC combustion.…”
Section: Influence Of Dual Component Interaction On No X Emissionmentioning
confidence: 99%